(untitled) (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we establish the existence of a common fixed point from a pair of set-valued mappings. By utilizing the concept of convergence of set-valued mappings’ sequences, both ordinary and pointwise convergence, we establish a common fixed point theorem. This our newly result is a generalization of common fixed point theorem of set-valued mappings on partial metric spaces. Further, we establish newly common fixed point theorem under φ-contraction on partial metric spaces.